Integration of Life Cycle Assessment and Policy Analysis for Improving Sustainable Coal Ash Management: A Case Study in South Sumatra, Indonesia - Pawitra, Yuga Prayna; Bayuaji, Ridho; Nadlifatin, Reny; Wahyuono, Ruri Agung (Journal Research of Social Science, Economics, and Management, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:578d73fc-8e9b-47bd-8c38-9700a61868d6-1" data-testid="conversation-turn-4" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="61b0d4fc-ca61-4387-a911-5299590c63e7" data-message-model-slug="gpt-4o-mini" data-turn-start-message="true"> FABA production in South Sumatra reaches 1.2–1.8 million tons annually, yet landfill disposal dominates and causes significant environmental impacts (LCA score: 40.29). The reclassification of FABA as non-hazardous waste under Government Regulation No. 22/2021 creates utilization opportunities; however, evidence-based regional policies remain limited. This research examines the integration of LCA and policy analysis to formulate recommendations for sustainable FABA management in South Sumatra. A convergent parallel design was applied, using LCA to compare landfill, paving block, and compost scenarios, and AHP involving 33 stakeholders to prioritize policy criteria and alternatives. LCA results show that compost has the lowest environmental impact (5.62), followed by paving blocks ( 18.00) and landfill (40.29). AHP prioritizes environmental (32.0%) and social (24.5%) aspects, with compost as the top alternative (46.5%). The LCA–AHP integration indicates strong alignment between scientific evidence and stakeholder preferences. Based on these results, policy recommendations are proposed across short-, medium-, and long-term horizons, supported by a stakeholder responsibility matrix to ensure effective implementation. The study provides integrated policy recommendations and supports circular economy development, multi-criteria decision-making, and SDGs 12, 13, and 15, positioning South Sumatra as a potential model for sustainable FABA management